Penentuan Kelayakan Lokasi Wifi.Id Corner Dengan AHP-PSO (Studi Kasus: Telkom Kota Kediri) - Ulfa Lina Wulandari; Dian Eka Ratnawati; Mochammad Ali Fauzi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Wifi.id Corner (wico) is a public facility of innovation from Telkom in the form of a place that provides internet access with high speed up to 100 Mbps. Currently, the determination of the location of Wifi.id Corner Telkom Kediri is done based on the consideration of the parties and managers of Wireless Broadband Division (DWB). So often have difficulty in determining the feasibility of installation location Wifi.id Corner from several proposed locations. This is due to the difficulty to determine the feasibility of location and which location can provide maximum benefits for the community and for Telkom Kediri. In determining the feasibility of Wifi.id Corner location there are 4 criteria by the company. There are the availability of network, users crowded, location type and density of Wifi.id Corner around the location. To solve this problem used Analytic Hierarchy Process (AHP) and Particle Swarm Optimization (PSO) methods. PSO is used to optimize the value of comparison matrix weight in AHP. The length of the used dimension is 6. Where each dimension value represents the comparative value of each criteria in the comparison matrix. In this research used 50 data location of Wifi.id Corner Telkom Kediri. From the test results obtained by the average fitness value of 0,94 with parameters of threshold value of 0,018, size of particles is 250 and number of iteration is 10 so that the obtained accuracy is 94%.